Regiochemistry of Camphor Analog Oxidation by Pseudomonas putida - Banerjee, Sujit (1983)
Pseudomonas putida cooxidized norcamphor and pericyclocamphanone to hydroxylated and lactonized products during growth on camphor. Norcamphor was hydroxylated at the 5 position, similar to the corresponding process in camphor, but pericyclocamphanone was oxidized at the 6 position. We conclude that the regiochemistry of the hydroxylation may be substrate controlled.